Decentralized Environmental Regulations and Plant-Level Productivity - Vivek Ghosal; Andreas Stephan; Jan F. Weiss (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using a unique plant-level dataset we examine total factor productivity (TFP) growth and its components, related to efficiency change and technical change. The data we use is from Sweden and for their pulp and paper industry, which is heavily regulated due to its historically large contribution to air and water pollution. Our paper contributes to the broader empirical literature on the Porter Hypothesis, which posits a positive relationship between environmental regulation and “green” TFP growth of firms. Our exercise is innovative as Sweden has a unique regulatory structure where the manufacturing plants have to comply with plant-specific regulatory standards stipulated at the national level, as well as decentralized local supervision and enforcement. Our key findings are: (1) prudential regulation limits expansion of plants with high initial pollution; (2) regulation, however, is not conducive to plants' “green” technical change, which provides evidence against the recast version of the Porter Hypothesis; (3) decentralized command-and-control regulation is prone to regulatory bias, entailing politically motivated discriminatory treatment of plants with otherwise equal characteristics.
Keywords: D24; L51; L60; Q52; Q53; Q58; 330; pollution; environmental regulations; plant-specific regulation; decentralized regulation; enforcement; political-economy; Porter Hypothesis; TFP; productivity; efficiency; technical change; pulp and paper industry